The Importance of Primary Health Care in Patients Affected by Covid-19 (Research, Society and Development, 2020)
This article aims to analyze the importance of primary care in patients affected by Covid-19. The current study is characterized as a review of integrative literature of the exploratory and explanatory type, with a qualitative approach. To carry out this study, the following databases were consulted: MEDLINE, Scholar google and SCIELO. DeCS was used in an associated way: Covid-19, Primary Care, Coronavirus and care, available in Portuguese and English and published between the years 2017 to 2020 It can be seen that of the 8 selected articles, 50% (4) of the articles selected were preceded by Scholar google and 50% (4) by Scielo. In addition, it was found that 100% (8) of the articles used were from the year 2020. The articles are widely discussed, in several aspects, such as the importance of PHC in patients with covid-19 patients and how to prevent the virus. Furthermore, among the selected articles, it is noted that the search for an effective therapy is constant in patients affected by covid-19, exhibiting new discoveries and increasingly expanding the possibilities available. The design of the respective correspond to a randomized clinical trial , literature reviews, cross-sectional studies and descriptive exploratory research. PHC plays a decisive role in health protection, in the prevention and control of infectious diseases through early diagnosis, treatment, follow-up and individual and family monitoring, being fundamental to the health / disease process. Infection control includes measures that reduce the risk of transmission in the unit itself, at home and in the community.